A high-power diode-pumped Nd:YVO4 slab amplifier with a hybrid resonator. (17th May 2016) - Mao, Y F; Zhang, H L; Yuan, J H; Hao, X L; Xing, J C; Xin, J G; Jiang, Y
Abstract: We demonstrated a compact and efficient in-band diode-pumped Nd:YVO4 partially end-pumped slab (Innoslab) nanosecond amplifier based on a hybrid resonator. For the seeder source, a-6 W, 5 ns Q -switched laser with a repetition rate of 30 kHz was obtained with beam quality factors M 2 < 1.3 . A beam-shaping system consisting of cylindrical lenses was designed according to the different sizes of the active medium in two orthogonal directions. A maximum average output power of 77 W was obtained. The optical-to-optical efficiency was 27.9%. The beam quality factors M 2 in the unstable and stable directions were 1.52 and 1.36, respectively.